Enhanced reductive dechlorination of trichloroethene with immobilized Clostridium butyricum in silica gel. (January 2020) - Lo, Kai-Hung; Lu, Che-Wei; Lin, Wei-Han; Chien, Chih-Ching; Chen, Ssu-Ching; Kao, Chih-Ming
Abstract: Deteriorated environmental conditions during the bioremediation of trichloroethene (TCE)-polluted groundwater cause decreased treatment efficiencies. This study assessed the effect of applying immobilized Clostridium butyricum (a hydrogen-producing bacterium) in silica gel on enhancing the reductive dechlorination efficiency of TCE with the slow polycolloid-releasing substrate (SPRS) supplement in groundwater. The responses of microbial communities with the immobilized system (immobilized Clostridium butyricum and SPRS amendments) were also characterized by the metagenomics assay. A complete TCE removal in microcosms was obtained within 30 days with the application of this immobilized system via reductive dechlorination processes. An increase in the population of Dehalococcoides spp. was observed using the quantitative polymerase chain reaction (qPCR) analysis. Results of metagenomics assay reveal that the microbial communities in the immobilized system were distinct from those in systems with SPRS only. Bacterial communities associated with TCE biodegradation also increased in microcosms treated with the immobilized system. The immobilized system shows a great potential to promote the TCE dechlorination efficiency, and the metagenomics-based approach provides detailed insights into dechlorinating microbial community dynamics. The results would be helpful in designing an in situ immobilized system to enhance the bioremediation efficiency of TCE-contaminated groundwater. Highlights: Immobilized Cloristridium butyricum ( C. butyricum ) can enhance TCE dechlorination. Growth of C. butyricum can be supported by slow polycolloid-releasing substrates. Desulfovibrio sp. and Conamonas sp. played important roles in TCE dechlorination. Increased DHC and microbial community in the immobilized system were observed. Methanogens inhibit the dechlorinators and decrease the dechlorination activity.